Role of Posterior Interfacetal Distraction and Grafting in Complex Atlantoaxial Dislocation - Mohamed Ali El-Gaidi, MD. (Egyptian Spine Association, 2019)
Background Data: Atlantoaxial fixation, unlike subaxial spine, is still challenging due to complex topographical anatomy. Nowadays, atlas lateral mass screws and transpedicular axis screws fixation is a well-accepted technique for the management of atlantoaxial instability due to their rigid fixation and higher fusion rate. However, in complex cases like basilar invagination, further reduction and proper bony alignment are needed. Study Design: A retrospective descriptive clinical case series. Objective: The aim of this study was to assess the safety and efficiency of bilateral posterior atlantoaxial facet joint distraction and insertion of spacer in reducing complex cases of atlantoaxial instability. Patients and Methods: Out of 17 patients with atlantoaxial instability, five patients underwent posterior fixation and atlantoaxial facet joint distraction and insertion of spacer for reduction of irreducible atlantoaxial dislocation. Clinical results were evaluated by using the criteria of Japanese Orthopaedic Association Scoring System for Cervical Myelopathy (JOA score). The surgical technique, results, and morbidity and mortality were assessed. Results: There were 3 females and 2 males; the age ranged from 10–50 years. The cause of significant instability was trauma (2 patients), while each of the 3 other patients suffered from Down syndrome, rheumatoid arthritis, and posttuberculous infection. All 5 patients had pyramidal tract compression manifestations. At the end of follow-up (mean 18 months), the average preoperative JOA score improved from 13.2±1 to 15.9±0.2 (P=0.04) and the average recovery rate was 69±12 % SD. Postoperative CT scans showed that the mean atlantodens interval improved from 6.2±1.6 to 1.8±0.8 (P=0.04) and the mean clivus-canal angle increased from 119.8±3.7° to 135.2±7°(P=0.04). The average extra time and blood loss of bilateral facet distraction and grafting were about 65 ml (P=0.004) and 72.5 ml, respectively. There was no mortality, vertebral artery injury, CSF leak, or construct failure. Conclusions: Bilateral posterior atlantoaxial facet joint distraction and placement of spacer is a safe and effective adjunct procedure for reduction of complex atlantoaxial instability. (2019ESJ184)